Clinical presentation and course of bleeding events in patients with venous thromboembolism, treated with apixaban or enoxaparin and warfarin - Bleker, Suzanne M.; Cohen, Alexander T.; Büller, Harry R.; Agnelli, Giancarlo; Gallus, Alexander S.; Raskob, Gary E.; Weitz, Jeffrey I.; Curto, Madelyn; Sisson, Melanie; Middeldorp, Saskia (Thrombosis and Haemostasis, 2016)
Apixaban, a direct acting oral anticoagulant (DOAC), was found to be non-inferior to and safer as enoxaparin followed by warfarin for treatment of venous thromboembolism (VTE) in the AMPLIFY trial. Information is needed on how bleeding events with DOACs present and develop. In this post-hoc analysis, the clinical presentation and course of all major and clinically relevant non major (CRNM) bleeding events in the AMPLIFY trial were blindly classified by three investigators, using predesigned classification schemes containing four categories. Odds ratios (OR) for classifying as category three or four (representing a more severe clinical presentation and course) were calculated between apixaban and enoxaparin/warfarin. In total, 63 major and 311 CRNM bleeding events were classified. Of the major bleeds, a more severe clinical presentation occurred in 28.5% of apixaban versus 44.9% of enoxaparin/warfarin related recipients (OR 0.49, 95% confidence interval [CI] 0.14–1.78). A severe clinical course was observed in 14.3% and in 12.2%, respectively (OR 1.19, 95%CI 0.21–6.69). Of the CRNM bleeding events, a more severe clinical presentation and extent of clinical care was found in 25% of apixaban recipients compared to 22.7% in the enoxaparin/warfarin group (OR 1.13, 95%CI 0.65–1.97). The clinical presentation and course of major and CRNM bleeds were similar in apixaban and enoxaparin/warfarin treated patients. This finding should reassure physicians and patients that even in the absence of a specific reversal agent, apixaban is a convenient and safe choice for VTE.
Keywords: Anticoagulants; apixaban; coumarins; haemorrhage; venous thromboembolism